Level Of Knowledge Mother About Stimulation Growth In Children's Age Development Age 4-6 Years - Ariani, Ni Komang Sri; Indriana, Ni Putu Riza kurnia (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Parents as caregivers but also as educators should know that children from an early age begin to emerge new skills, both physical and mental skills. In parenting a child, parents need to understand what is happening to the child and recognize what the child needs for his development, as well as what things must be done to meet those needs. Objectives: to find out how the level of knowledge of mothers about the growth and development of preschool children aged 4-6 years. Methods: Descriptive using Non Probability Sampling, a sample of 40 respondents who met the inclusion criteria. Results: From 40 respondents, the majority of respondents aged 24-33 years, 25 respondents (62.5%) obtained data, and 19 respondents (47.5%) obtained high school education. Most respondents have a good level of knowledge about the stimulation of their children's growth and development, this can be seen from the results of the questionnaire all respondents answered statement number 1 correctly, meaning that all respondents understood about the meaning of growth and stimulation. Almost all respondents understand about the forms of stimulation, this can be seen from almost all respondents answering statements number 2 to number 9 correctly, only 5% of respondents answered incorrectly. Almost all respondents also have knowledge about stimulation in preschool children aged 4-6 years, this can be seen from almost all respondents answering statements number 11 to number 20 correctly, only 15 (%) respondents answered incorrectly. Discussion: Most respondents have a good level of knowledge about their children's growth and development stimulation.